2022
DOI: 10.1101/2022.05.04.490614
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Omicron subvariants evolved to promote further escape from MHC-I recognition

Abstract: SummarySARS-CoV-2 variants of concern (VOCs) possess mutations that confer resistance to neutralizing antibodies within the Spike protein and are associated with breakthrough infection and reinfection. By contrast, less is known about the escape from CD8+ T cell-mediated immunity by VOC. Here, we demonstrated that VOCs retain similar MHC-I downregulation capacity compared to the ancestral virus. However, VOCs exhibit a greater ability to suppress type I IFN than the ancestral virus. Although VOCs possess uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 73 publications
0
20
0
1
Order By: Relevance
“…Two days after transduction of human 293T cells, we measured MHC-I surface levels by flow cytometry using a pan-HLA class I-reactive monoclonal antibody. Expression of ORF7a reduced MHC-I levels on the cell surface by approximately 5-fold, whereas expression of other individual viral proteins (notably including ORF8 (16, 17)) had no effect on MHC-I surface levels (Figure 1). We also examined the impact of SARS-CoV-2 ORFs on the expression of tetherin, a cell surface antiviral protein that traps enveloped virions from various virus families that bud through cell membranes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two days after transduction of human 293T cells, we measured MHC-I surface levels by flow cytometry using a pan-HLA class I-reactive monoclonal antibody. Expression of ORF7a reduced MHC-I levels on the cell surface by approximately 5-fold, whereas expression of other individual viral proteins (notably including ORF8 (16, 17)) had no effect on MHC-I surface levels (Figure 1). We also examined the impact of SARS-CoV-2 ORFs on the expression of tetherin, a cell surface antiviral protein that traps enveloped virions from various virus families that bud through cell membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there are several reasons to think that MHC-I downregulation might be an evolved property in sarbecoviruses. Some recent studies have suggested that SARS-CoV-2 ORF8 protein induces MHC-I downregulation(16, 17). We did not observe such an effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the functional consequence of localization of ORF7a we have observed, we suggest that studies employing C-terminally tagged ORF7a need to be interpreted with caution. However, a recent report that has not been peer-reviewed found that C-terminally tagged ORF7a was capable of downregulating MHC-I in HEK293T cells(37). While we expressed ORF7a-ARA in an inducible manner, the tagged ORF7a was transiently expressed, and we are investigating whether this or other mechanisms account for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…Besides ORF7a, multiple studies have identified SARS-CoV-2 gene products to interfere with MHC-I expression. A recent preprint showed that several SARS-CoV-2 gene products have the capacity to downregulate MHC-I molecules, including the viral E, M, ORF7a, ORF7b, and ORF8 proteins [51]. In this study, no additional experiments were performed to address the nature of MHC-I regulation.…”
Section: Discussionmentioning
confidence: 99%